Surface application of lime-silicate-phosphogypsum mixtures for improving tropical soil properties and irrigated common bean yield - Crusciol, Carlos A.C. [UNESP]; Artigiani, Angela C.C.A. [UNESP]; Arf, Orivaldo [UNESP]; Carmeis Filho, Antonio C.A. [UNESP]; Soratto, Rogerio P. [UNESP]; Nascente, Adriano S.; Alvarez, Rita C.F. (Wiley, 2016)
The movement of surface-applied lime to subsurface soil layers is slow, and, consequently, liming requires a long period of time to become effective. Thus, it is important to develop strategies to increase the efficiency of acidity amendments practices in order to improve the chemical properties of tropical acid soils in no-till systems. The aim of this study was to evaluate the effects of applying mixtures of silicate, lime, and phosphogypsum to the soil surface in tropical no-till systems on soil chemical properties and leaf nutrient concentrations, yield components, and grain yield of the common bean (Phaseolus vulgaris L.). A field experiment was performed during two growing seasons (2004 and 2005) in a field with Typic Acrustox soils. Among the treatments, the silicate-phosphogypsum mixture was more effective for ameliorating soil acidity at a depth of 0 to 0.20 m over a short period of time (6 mo). The application of soil amendments separately or in mixtures increased the soil pH to 0.40 m depth 18 mo after application. Combining the surface application of phosphogypsum with lime and/or silicate effectively increased the NO3-N, SO4 2--S, and Ca2+ levels at soil depths of up to 0.40 m over a relatively short period of time, resulting in a higher base saturation in the deepest layer evaluated (0.20-0.40 m). Compared with the control treatment, the mixtures of soil acidity amendments and phosphogypsum resulted in greater Ca, S, and Si concentrations in the leaves and increased the grain yield of the common bean by >22% over two growing seasons. Long-term studies are required to establish the frequency of reapplication and the residual effects of soil amendment mixtures.